2019
DOI: 10.3390/su11123375
|View full text |Cite
|
Sign up to set email alerts
|

Is Corporate Social Responsibility Used to Mask Corporate Speculation? Evidence from Emerging China

Abstract: Why do rational, profit-orientated firms generously engage in corporate social responsibility (CSR)? Our study explores the real motives of speculative firms for CSR engagement and the hidden causality behind it. Using national survey data of privately owned firms in China, we find that corporate speculation positively influences firms’ engagement in CSR, revealing that CSR is instrumental and that firms use it as a tool to mask their speculative activities by building their reputations and buying ‘leniency in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 74 publications
(186 reference statements)
0
7
0
Order By: Relevance
“…Internal drivers of corporate social responsibility Some studies have assessed the various internal factors acting as drivers of CSR (Agudo-Valiente et al, 2017;Al-Reyaysa et al, 2019;Fabrizi et al, 2014;Galbreath, 2010;Hu et al, 2018;Ikemba-Efughi and Raj, 2020: Kachouri et al, 2020: Kim and Lee, 2012Kolk et al, 2014;Lee et al, 2018;Lenssen et al, 2011;Li et al, 2016;Miska et al, 2016;Mzembe et al, 2016;Orazalin, 2019;Park and Ghauri, 2015;Reddy and Hamann, 2018;Reimann et al, 2015;Rodríguez Bolívar et al, 2015;Shirodkar et al, 2018;Sui et al, 2019;Valls Martinez et al, 2019;Yin, 2017). Firms engage in CSR because of internal institutional factors such as ethical corporate culture and top management commitment (Yin, 2017).…”
Section: Consequences Of Global Corporate Social Responsibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Internal drivers of corporate social responsibility Some studies have assessed the various internal factors acting as drivers of CSR (Agudo-Valiente et al, 2017;Al-Reyaysa et al, 2019;Fabrizi et al, 2014;Galbreath, 2010;Hu et al, 2018;Ikemba-Efughi and Raj, 2020: Kachouri et al, 2020: Kim and Lee, 2012Kolk et al, 2014;Lee et al, 2018;Lenssen et al, 2011;Li et al, 2016;Miska et al, 2016;Mzembe et al, 2016;Orazalin, 2019;Park and Ghauri, 2015;Reddy and Hamann, 2018;Reimann et al, 2015;Rodríguez Bolívar et al, 2015;Shirodkar et al, 2018;Sui et al, 2019;Valls Martinez et al, 2019;Yin, 2017). Firms engage in CSR because of internal institutional factors such as ethical corporate culture and top management commitment (Yin, 2017).…”
Section: Consequences Of Global Corporate Social Responsibilitymentioning
confidence: 99%
“…Consumers expect that firms engage in CSR initiatives that sincerely serve public interests and at the same time attend to firm-serving motives (Kim and Lee, 2012). Notwithstanding, the real motive that drives the CSR activities of organisations, is to manage potential risks from their speculative activities suggesting that firms may act in more self-serving ways under the guise of CSR (Sui et al, 2019). Consumer expectations with respect to CSR in China combine both economic and legal responsibility (required CSR) and philanthropic responsibilities and ethical responsibilities (expected CSR).…”
Section: Consequences Of Global Corporate Social Responsibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Such organisations rely on CSR as a means of minimising uncertainty regarding access to resources essential for their operations. In addition, Sui et al (2019) found that corporate speculation influences CSR engagements positively. Firms employ CSR as a means to conceal their speculative activities by establishing their status and acquiring leniency insurance against possible penalties.…”
Section: Resultsmentioning
confidence: 99%